The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.ijrmms.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Frictionless shear at great depth and other paradoxes of hard rocks

Abstract: Shearing with very low friction is regarded as responsible for the high energy release from deep-seated earthquakes and rock bursts in deep underground mines, but in spite of considerable attention to the problem no consensus of opinion has been reached regarding the physical explanation for the low friction. Alternative hypotheses include melting, lubrication, excess pore pressure, velocity effects and vibration at the interface. Here, however, we demonstrate that under high confining stresses shear fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
(43 reference statements)
1
34
0
Order By: Relevance
“…The coal burst source is the mechanism that triggers or induces the damage mechanism visible on the excavation surface. The coal burst source is generally associated with a seismic event that can be performed at a wide range of local magnitudes [1][2][3][4][5][6]. Indeed, mining-induced seismicity can reach moderate values of ground velocity and acceleration, and in some cases on the surface may lead to the generation of low-intensity earthquakes [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coal burst source is the mechanism that triggers or induces the damage mechanism visible on the excavation surface. The coal burst source is generally associated with a seismic event that can be performed at a wide range of local magnitudes [1][2][3][4][5][6]. Indeed, mining-induced seismicity can reach moderate values of ground velocity and acceleration, and in some cases on the surface may lead to the generation of low-intensity earthquakes [7].…”
Section: Introductionmentioning
confidence: 99%
“…This sudden shear displacement can result in the generation of vibrations that cause coal ejections when they are situated near the excavation boundaries [5]. Tarasov and Randolph [6] devoted special attention to comprehensively elaborating the individual and inconsistent behaviours of hard rock at the significant depth, which are directly in line with the rock fracture condition in deep excavations. Tarasov and Randolph [6] broadly indicated that the shear failure procedures, under the significantly low frictional condition between the engaged surfaces, can be classified as the main reason for the release of energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coal burst source is the mechanism that triggers or induces the damage mechanism visible on the excavation surface. The coal burst source is generally associated with a seismic event that can be performed at a wide range of local magnitudes, normally ranging from undetectable up to 5 [6]. Indeed, mining-induced seismicity can reach moderate values of ground velocity and acceleration, and in some cases its effects on the surface can be compared with low-intensity earthquakes [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the place of the source of the energy, where it is located in a plane of weakness inside the coal mass, the released energy provokes shear displacement along the plane, which in revolve generate vibrations that persuade coal ejections when they are situated near the excavation boundaries [7]. Tarasov and Randolph [6] have explained a number of special and inconsistent behaviours of hard rock at the significant depth that are directly related to rock failure mechanisms in deep excavations. They determined that the procedures of the shear failure, with respect to the significant low friction, can be classified as the main reason to release energy.…”
Section: Introductionmentioning
confidence: 99%